385 MIR-24-3P REGULATES CDX2 DURING THE PROCESS OF INTESTINALIZATION OF THE CARDIAC-TYPE EPITHELIUM IN A HUMAN MODEL OF BARRETT'S ESOPHAGUS. (17th September 2021) - Pera, Manuel; Garrido, Marta; Gil, Gabriel; Fassan, Matteo; Climent, Marta; Nonell, Lara; Anglada, Roger; Iglesias, Mar; Guzzardo, Vicenza; Borga, Chiara; Grande, Luis; Bolós, Carme
Abstract:  : Cardiac-type epithelium has been proposed as an intermediate stage between normal squamous epithelium and intestinal metaplasia in the development of Barrett's esophagus. Deregulation of certain miRNAs and their effects on CDX2 expression might contribute to the intestinalization process of cardiac-type epithelium. The aim of this study was to identify miRNAs differentially expressed between CDX2 positive and negative glands of Barrett's esophagus and to examine the function of specific miRNAs on the regulation of CDX2. Methods: miRNA expression profiling using OpenArrayTM analysis in microdissected cardiac-type glands with and without fully CDX2 expression was performed in biopsies from patients who developed cardiac-type epithelium in the remnant esophagus after esophagectomy. Data were validated using real-time PCR in esophageal adenocarcinoma cell lines and in situ and real-time PCR miRNA/CDX2/MUC2 co-expression analysis in cardiac-type mucosa samples. The effect of miR-24-3p precursor transfection on CDX2 expression was assessed in the esophageal adenocarcinoma cell lines FLO-1 and KYAE-1. Results: CDX2 positive glands were characterized by an unique miRNA profile with a significant downregulation of miR-24-3p, miR-520e-3p, miR-548a-1, miR-597-5p, miR-133a-3p, miR-30a-5p, miR-638, miR-625-3p, miR-1255b-1, miR-1260a and upregulation of miR-590 (Figure 1A). miRNA-24-3p was identified as potential regulator of CDX2 gene expression in three bioinformatics algorithms, and this was confirmed in esophageal adenocarcinoma cell lines (Figure 1C). Furthermore, miR-24-3p expression negatively correlates with CDX2 in cardiac-type mucosa samples with different stages of mucosal intestinalization (Figure 1B). Conclusion: These results imply that miRNA-24-3p directly targets CDX2, and downregulation of miRNA-24-3p is associated with the acquisition of an intestinal phenotype in cardiac-type epithelium.